South African Grade 9 Mathematics Teachers' Views on the Teaching of Problem Solving. Issue 1 (2nd January 2018) - Chirinda, Brantina; Barmby, Patrick
Abstract : The South African curriculum emphasizes the teaching of problem solving in mathematics. However, little is known about South African teachers' views on the teaching of mathematical problem solving (MPS). The purpose of this study was to establish Grade 9 South African teachers' views, teaching strategies and the support required in their teaching of MPS. We worked with teachers who teach MPS to large, under-resourced and multilingual classes. Data for the study were collected using an open-ended questionnaire and classroom observations. The questionnaire sample consisted of 31 teachers from 20 schools in a district in Gauteng, South Africa. Data was analysed through grounded theory techniques and the findings indicate that overcrowded classes and learners' problems with English as the language of learning and teaching compel teachers to retain strict ownership of the MPS process. The findings also uncovered that teachers' adoption of the MPS as a step-by-step guided sense-making strategy is a response to learners' perceived lack of mastery of basic algorithms. All participants in the study stated that they required support on the teaching of MPS that included practical demonstration of MPS pedagogy in the context of their classes where discipline is a challenge and learners are under-prepared, lack basic MPS skills and struggle with the language of learning and teaching.